In Silico Study of Compounds in Bawang Dayak (Eleutherine palmifolia (L) Merr.) Bulbs on Alpha Estrogen Receptors - Sunani, Sunani; Andani, Maya; Kamaludin, Asilla Mauri Ramdini; Helmi, Nyai Ayu Sylfia Stannia Puspitasari; Mei, Kaila Keyshia; Guspira, Yunitasya; Sabetta, Oktavia; Aulifa, Diah Lia (Indonesian Journal of Cancer Chemoprevention, 2022)
Breast cancer is an uncontrolled malignancy of the breast that originates from glandular cells, gland ducts, and the supporting tissues of the breast. The development of herbal-based anticancer drugs is progressing, one of which is derived from the natural ingredients of Eleutherine palmifolia tubers. The aim of this study was to determine the activity of compounds derived from Eleutherine palmifolia tubers on the alpha-estrogen receptor (ERα) using an in silico study. The crystal structure of the enzyme used was 3ERT which was obtained from the Protein Data Bank (PDB). The applications used in this journal are Chem3D (initial preparation of ligands and receptors), AutoDock4 (redocking and calculation of root mean square deviation (RSMD)), and Biovia (visualization of redocking results). Tamoxifen was used as a reference ligand. Based on the results of the in silico study, the best compound that has the potential to be developed as a candidate for anticancer drug is Eleutherine because the results of the in silico test on Eleutherine have a value of G=-7.56 kkal/mol and the smallest KI=2.89 nM, so it can be concluded that eleutherine is one of potential drug candidate for anti cancer.Keywords: Breast cancer, eleutherine, estrogen receptor α.